Cryptography System Based on SEMT Labeling of Total Path and Its Application for Securing Image File by Using Android Studio - Trisha Magdalena Adelheid Januaviani; Bahrirrudin Bahrirrudin; Nikita Nikita; I Wayan Sudarsana; Nasria Nacong; Agusman Sahari; Hajar Hajar; Selvy Musdaifah; Moh Ali Akbar; Tri Prasetia Ningrum (JURNAL SISFOTEK GLOBAL, 2026)
Cryptography is one of the mathematical techniques used to address information security issues. The study of information security is essential due to the rapid development of information technology, which increases the risk of unauthorized access to sensitive data. Android smartphones are among the most popular communication devices, offering various features such as text messaging, image sharing, audio, video, and more. Given people use Android widely, data stored on Android devices is highly vulnerable to hacking attempts. Therefore, a cryptographic approach based on graph labeling will be applied to secure images on Android smartphones. This method utilizes the Super Edge Magic Total (SEMT) labeling for total path graphs to encrypt and decrypt image pixels, ensuring the security of images. Furthermore, this technique will be implemented to develop an Android-based application using Android Studio. The study results indicate that total path graphs satisfy the SEMT labeling properties and the developed application functions effectively on Android devices to secure images.